Global Economic Trends and Their Impact on International Accounting Standards: A Comparative Analysis - T. Malibiran, Leonora; Jose H. Leyba, Ceazar (CV. Lafadz Jaya, 2025)
This paper explores the evolving relationship between global economic trends and accounting practices, with a particular focus on the adoption and impact of International Financial Reporting Standards (IFRS). The study examines how economic globalization, financial crises, and technological advancements have shaped accounting standards and practices worldwide. Globalization has driven the need for harmonized accounting standards to enhance comparability and transparency in financial reporting across borders. However, the pace of IFRS adoption varies, with challenges in emerging markets due to differences in legal systems, financial infrastructures, and institutional readiness. The 2008 global financial crisis highlighted the shortcomings of existing accounting frameworks, particularly in terms of fair value accounting, leading to calls for more robust and transparent financial reporting mechanisms. Technological advancements, including the rise of artificial intelligence (AI), blockchain, and automated financial reporting, are transforming the accounting profession, presenting both opportunities and challenges. While these technologies promise greater efficiency and accuracy, they also introduce new risks, such as cybersecurity threats and data manipulation concerns. The findings underscore the need for continued reform and collaboration among international bodies to create adaptable and responsive accounting standards that can meet the demands of an ever-evolving global economic landscape.